Modern methods of influence at endometrial receptivity in patients with recurrent implantation failure (review) - M I Polovneva; I E Korneeva; O V Bourmenskaya (IP Berlin A.V., 2018)
Objective. To carry out an analysis of the data available in scientific literature on modern methods of influence at endometrial receptivity in patients with recurrent implantation failure. Materials and methods. The review includes the data of foreign and Russia papers published on PubMed during the last 7-10 years. Results. There are studies described the role of endometrial scratching, infusion granulocyte colony stimulating factor, autologous peripheral blood mononuclear cells, autologous platelet-rich plasma, the endometrial receptivity array in treatment for patients with repeated implantation failure. Conclusion. Several adjuvant therapies and diagnostic tests have been used along with IVF to increase the pregnancy rates for women with repeated implantation failure. Perhaps a new test-system to find personal predictors of endometrial receptivity can tern up a positive effect at patients with RIF.